Pengaruh Metode Multisensori VAKT (Visual, Auditory, Kinesthetic, Tactile) terhadap Kemampuan Pengetahuan Abjad Siswa SD - Sani, Mutiara Nabila Purnama; Kusumaningrum, Syams; Asrul (STKIP Andi Matappa Pangkep, 2024)
This research aims to determine the effect of using the Multisensory VAKT (Visual, Auditory, Kinesthetic, Tactile) Method on the Alphabet Knowledge Ability of Class II Students at SDN 42 Sorong City. This research uses a pre-experiment quantitative research method with a One Group Pretest Posttest research design. The data in this study were analyzed using inferential statistical analysis techniques (Paired Sample T-test). The pretest results showed that the majority of students' alphabet knowledge at the start of the research was still in the